Lignin decomposition of Oil Palm Frond by Pleurotus ostreatus with a variation of corn and rice-husk media - Misri Gozan; Nadia Chrisayu Natasha; Penjit Srinophakun (Journal of Integrated and Advanced Engineering (JIAE), 2022)
This study aimed to decompose lignin from oil palm midrib (OPF) bonds using the fungus Pleurotus ostreatus with various substrates (corn and rice husk). Lignin and cellulose levels before and after mushroom culture were tested by the Chesson-Datta method. Substrate variation with corn and husk rice showed that the addition of corn did not play a role in lignin decomposition. After being given treatment, the best degradation was using 0.6 grams of rice bran and 0.4 grams of CaCO3, 22.01% for lignin and 32.74% for cellulose.